2023
DOI: 10.3389/fimmu.2023.1084630
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term immune responses to SARS-CoV-2 infection in unvaccinated children and young adults with inborn errors of immunity

Abstract: PurposeTo describe SARS-CoV-2 infection outcome in unvaccinated children and young adults with inborn errors of immunity (IEI) and to compare their specific acute and long-term immune responses with a sex-, age-, and severity-matched healthy population (HC).MethodsUnvaccinated IEI patients up to 22 years old infected with SARS-CoV-2 were recruited along with a cohort of HC. SARS-CoV-2 serology and ELISpot were performed in the acute phase of infection (up to 6 weeks) and at 3, 6, 9, and 12 months.ResultsTwenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…However, Cousins et al, also reported that the Mount Sinai cohort over time have been less ill and required less hospitalization, in accordance to general population. Another study in IEI pediatric to young adults, reported higher COVID-19 pneumonia rate that the general age-range population with lower humoral and cellular responses in the acute phase ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Cousins et al, also reported that the Mount Sinai cohort over time have been less ill and required less hospitalization, in accordance to general population. Another study in IEI pediatric to young adults, reported higher COVID-19 pneumonia rate that the general age-range population with lower humoral and cellular responses in the acute phase ( 44 ).…”
Section: Discussionmentioning
confidence: 99%